Dampak Influencer Instagram Terhadap Gaya Hidup Belanja Impulsif Pada Remaja di Batam - Eric Eric; Jocelyn Jocelyn; Andrew Cen; Valenteeno Bong; Felix King Lie (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Instagram users who are dominated by teenage users have become even more popular as a place to endorse by influencers. Teenagers who are still not mature enough in shopping are also targeted in making purchase impulsively. This study aims to analyze the impact of Instagram’s influencers on impulsive shopping lifestyle in adolescents in Batam. The research was done by collecting data using questionnaires and was analyzed using SEM and AMOS. The result showed that brand attitude and product attractiveness which were significantly influenced by attractiveness, expertise, and trustworthiness variables had a significant effect on impulsive buying intentions variables. The success of this endorsement is then used as a strategy to increase sales owned by product brands that target their market share in the teenager group.